Relationship between orofacial dysfunction and orofacial features, oral function, and eating performance among preschool children - Mei-Chen Chang; Hsiu-Lin Chen; Shun-Te Huang; Hsiao-Ping Wang; Hsiu-Yueh Liu (Elsevier, 2024)
Background/purpose: Orofacial (OF) development is influenced by multiple factors. This study aimed to explore the relationship between OF dysfunction (OFD) and OF features, oral function, and eating performance among preschool children. Materials and methods: There were 243 preschool children and their parents who participated in this cross-sectional study. Participant demographic information and eating performance were obtained from questionnaires completed by their mothers. OF features and functions were assessed using oral examinations. OFD assessments were performed using Nordic Orofacial Test-Screening (NOT-S). Results: Approximately 80% of participants had at least one domain of NOT-S affected. The main OFD in a structured interview was chewing and swallowing (64.61%). Dysarthria (40.38%), weak bite force (53.85%), inability to effectively chew (45.19%), and taking longer than 30 min to eat meals (75.00%) were significantly more prevalent among participants with OFD than among those without OFD (all P < 0.05). Also, compared with participants born full-term, those born prematurely and who had OFD had higher rates of V-shaped dental arch (42.11%), high-arched palate (31.58%), small mouth opening capacity (7.89%), dysarthria (65.79%), preference to eating soft-textured food (42.11%), and weak cough strength (21.05%). Taking longer than 30 min to eat meals (adjusted odds ratio (AOR = 8.87, P < 0.001) and not effectively chewing food (AOR = 8.81, P < 0.001) were significantly associated with OFD. Conclusion: Chewing and swallowing and habits are common among preschool children and associated with OFD. OFD is associated with OF features, and presented in oral function and eating performance.